Effect of Stress and Water Pressure on Permeability of Fractured Sandstone Based on Response Surface Method - Bo You (Frontiers in Earth Science, 2020)
In order to study the effects of stress and water pressure on the permeability of fractured sandstone, an ultra-deep gas layer of fractured tight sandstone in WengFu Mine in GuiZhou province, was selected for experimental design and research, and the effects of confining pressure, internal pressure, effective stress, and water pressure on gas permeability were studied. The results show that the effective stress and slippage effect compete with each other when the confining pressure is kept fixed and the internal pressure is increased in the fractured tight sandstone reservoir. At the beginning of the experiment, the gas slippage effect is strong while the rock stress sensitivity is weak. The gas permeability increasingly decreases with the increase of internal pressure. The effective stress is stronger than slippage effect, and the gas permeability increases with the increase of internal pressure when crossing the low point of permeability. The greater the confining pressure is, the greater the internal pressure needed to reach the low permeability point will be. With the increase of axial stress, horizontal contact hydraulic hole increasingly closed. Horizontal hydraulic holes are more sensitive to axial stress than vertical ones.